Pengaruh Penerapan E-Samsat Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus Pada Wajib Pajak Di Samsat Kota Cimahi) - Latifa Novina Herawati; Vinny Stephanie Hidayat (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
This research aims to examine the impact of implementing e-samsat and tax sanctions on motor vehicle taxpayer compliance. This type of research is explanatory research with a quantitative approach. The population is taxpayers registered at the Cimahi Samsat Office. This study utilizes purposive sampling in sampling with the provisions of motor vehicle tax subjects registered at the Cimahi Samsat Office to obtain a sample of 40 respondents. The data collection technique for this study was in the form of a questionnaire/questionnaire which was distributed to several compulsory PKB at the Cimahi Samsat Office. The analysis prerequisite test utilizes heteroscedasticity testing, multicollinearity testing, normality testing, reliability testing, and validity testing using the help of SPSS 26, then multiple linear regression analysis and partial test (t test) with the help of SPSS 26. The results of the t-test indicate that the application of e-samsat partially has an impact on taxpayer compliance, while tax sanctions partially have no impact on taxpayer compliance. It is concluded that the variable of the implementation of e-samsat partially has an impact on taxpayer compliance, and the variable of tax sanctions partially has no impact on taxpayer compliance. The limitation of this research is that the sample used is only 40 respondents and the scope of the research is limited to only 1 Tax Office.